Inheritance and allelic relationships of anthracnose resistance in common bean paloma cultivar - Castro, S. A. L. (2014)
Anthracnose, caused by Colletotrichum lindemuthianum L., is one of the most important fungal diseases of common bean (Phaseolus vulgaris, L). Genetic resistance is the most effective method for this disease control. So far, twenty one resistance genes have been already characterized, and among them, only eight are Andean and due to it, the search for Andean resistance sources is really necessary. This way, the work aimed to characterize the genetic resistance of an Andean common bean cultivar.